LEGAL ANALYSIS OF FIDUCIARY GUARANTEES IN FINANCE COMPANIES: LEGAL ANALYSIS OF FIDUCIARY GUARANTEES IN FINANCE COMPANIES - Neneng Adelia (CV Rewang Rencang, 2024)
In statutory regulations Fiduciary guarantees are regulated in Law Number 42 of 1999. In the Law, explained then the meaning of The transfer of ownership of an object is called fiduciary based of confidence in these provisions then from the object that is the basis of the basis of ownership rights, namely, The movement always be within the limits of ownership of the object. The fiduciary on collateral itself namely a security right over movable objects, whether tangible or intangible, and in buildings that cannot be loaded, they are included as immovable objects, right of dependency contained in statutory regulation Number 4 the 1996 explaining the Right of Dependency that remains in the control of the Fiduciary, as collateral for the repayment of certain debts, which gives the Fiduciary a priority position over other creditors. So if it is concluded that a fiduciary guarantee is a guarantee certificate that will be given to a capital provider institution (which will provide credit) to ensure the timeliness of the payment of credit installments that have been given to creditors with collateral that has been collateralized in the form of goods and has been used as a credit contract. In the implementation of the research, the aim is to find out the functions and regulations begins with a guarantee from a fiduciary in Indonesia and what applies analysis of these guarantees for budget company. This research uses normative juridical research methods targeted at applicable laws, books, journals and other research results. The researcher was carried away to carry out the writing related to fiduciary guarantees with the title: